직접일자리사업 참여자의 일자리 이행에 관한 분석 - 최재문(Jae Moon Choi); 김경아(Kyoung Ah Kim) (재정학연구, 2025)
이 연구는 직접일자리사업 참여자(2020-2022)를 대상으로 사업 종료 후 일자리 이행의 관점에서 노동시장 성과를 분석하였다. 직접일자리사업은 정부가 제공하는 한시적 일자리로 중앙부처 고유목적에 따라 다양한 사업이 시행되고 있다. 사업 특성에 따른 재유형화를 통하여 노동시장이행A형 사업군(안전, 보존·보전·보호, 경력활용 및 서비스), 노동시장이행B형 사업군(전문인력, 청년층, 경단여성), 사회봉사·복지형 사업군 3가지로 구분하여 일자리 이행에 관한 콕스비례 위험 분석을 수행하였다. 분석 결과, 사회봉사·복지형을 기준으로 노동시장이행 B형이 A형보다 재취업 확률이 높게 나타나는데, 이는 상대적으로 B형에서 연령층이 젊고 인턴형 및 전문인력 등 일·경험 사업의 특성이 반영되어 사업 참여자들이 일자리 징검다리로서 효과적으로 직접일자리사업을 활용하고 있는 것으로 보인다. 재취업 후 고용유지율 측면에서는 사회봉사·복지형 참여자와 비교하여 노동시장이행 A형 참여자의 재취업 후 고용유지 확률이 가장 높았으며, 노동시장이행 B형 참여자의 고용유지 확률도 다음으로 높게 나타났다. 대체로 근로 형태가 상시직이면서 기업규모가 큰 곳에서 근무한 이력이 있는 경우 안정적인 이행 경로를 보인다. 앞서 재취업 분석과 유사하게 임금 효과 분석에서도 노동시장이행 B형에서의 임금 프리미엄의 효과가 높게 나타난다. 그러나 직접일자리사업 참여 종료 후 미취업으로 남아있는 인원이 많으므로 직업훈련, 고용서비스, 장려금 등 다른 일자리 사업유형과 원활한 연계가 필요할 것이다. This study analyzed the job transition and employment outcomes after the end of the project for participants of direct-job programs(2020-2022). The study categorized the projects into three types of projects: labor-market transition type A (safety, preservation-conservation-protection, career utilization and services), labor-market transition type B (professional workers, youth, career-breaking woman), and social service and welfare type projects, and conducted a Cox proportional hazard analysis on job transition. The analysis shows that the probability of reemployment is higher in Type B than Type A, which reflects the characteristics of work experience projects such as internships and professional workers, which are younger in age and reflect the characteristics of work experience projects, so it seems that borrowers are effectively using direct job projects as a bridge to employment. In terms of employment retention rate, the probability of retaining employment after reemployment was the highest for participants in the labor market program A, compared to participants in the social service welfare program, and the probability of retaining employment was the second highest for participants in the labor market program B. Those with a history of full-time employment and working for larger firms have a more stable transition path. Similar to the reemployment analysis above, the wage effect analysis shows that the wage premium in Labor Market Action B is high. However, since there are many people who remain unemployed after the end of participation in the direct job program, it is necessary to better connect with other types of matching programs such as vocational training, employment services, and incentives. KCI Citation Count: 0